Energy balance in the poultry-shed system and its influence on broiler performance - Silva,Tatiana P. N. da (2015)
ABSTRACT The objective of this study was to determine the energy balance of the poultry-shed system and its effect on broiler performance during the production cycle. The experimental design was completely random with sub-divided blocks. The blocks were composed of five different types of sheds and the sub-blocks of the evaluation times (00:00 h to 23:00 h), allowing an analysis of variance and a comparison between means with the Tukey test. There were no significant differences between the mean values of the exchanges of sensible, latent and total heat between the poultry sheds but the differences for the evaluation times were significant (P<0.05). There was no significant difference between sheds 1 and 4 for broiler productive performance regarding weight gain, feed consumption and feed conversion. Bird performance was significant (P<0.05) for the remaining poultry sheds. The productive indexes remained below the ranges considered ideal for broilers and values in the final weeks were characterized by the poor installation efficiency in controlling temperature variations and, consequently, the energy balance in the system, which adversely affected bird productive performance.